Precision Medicine in Mite Allergic Rhinitis - González-Pérez, Ruperto; El-Qutob, David; Letrán, Antonio; Matheu, Víctor (Frontiers in Allergy, 2021)
It is well known that a correct diagnosis is necessary for effective treatment. In the case of allergic rhinitis due to mites, imprecise diagnosis with effective but improvable methods means that in many cases an optimal result is not reached in patients. The diagnosis of allergic rhinitis due to mite sensitization have to require more homogeneously reproducible diagnostic tests that try to encompass many more of the protein antigens contained in them. With the few proteins that the problem has usually focused on, there is no they would cover many of the clinically relevant allergens in a large proportion of patients. In this mini-review we try to highlight the importance of having good allergenic sources and briefly gather information on various allergenic proteins included in mites that could be clinically relevant. All this to try to get closer to a more accurate diagnosis. We are also talking about two diagnostic tools that are clearly out of use and that should be promoted in the consultations to obtain an even greater and better outcome in patients.